Time trends in estimates of genetic parameters in a White Leghorn population subjected to long-term selection - CRATTERJEE, R N; MISRA, B S; SINGH, H N (The Indian Journal of Animal Sciences, 2013)
Pullets (3 813) of 185 sires and 1 403 dams of 9 consecutive generations were examined in the present study, Females, on the basis of their family averages and males, on the basis of sire family averages were selected for first 100 days egg production every generation. The traits taken were age at sexual maturity (ASM), body weight at sexual maturity (WAM), first 100 days egg production (EP 100), egg weight (EW) and average clutch size (CS), The phenotypic time trends for all these traits were nonsignificant except for EW which was negatively significant. The pooled heritability estimates were higher for ASM and EW, moderate for WAM and low for EPIOO and CS. The time trends of heritability estimates (b+- SE) were all negative and not significant. This indicated that additive genetic variance of the traits in the population were not reduced significantly. The pooled estimates of genetic, environmental and phenotypic correlation of ASM with WAM were all positive, while ASM with EP 100 and CS were mostly negative. The pooled estimates of genetic correlation between ASM and EW was positively significant (0.23 +-0.01) and moderate. The estimates of genetic correlation between WAM and EW were all positive and moderate to high, EP100 was positively correlated with CS but negatively correlated with EW, There was negative association between EW and CS. The time trends in estimates of genetic, environmental and phenotypic correlation were mostly not significant.